The Most Patient Man - "Khan, Saniyasnain" (Goodword Books: New Delhi, 2010)
"The Most Patient Man is a beautifully illustrated and creatively written story about the Prophet Ayyub."--Page 4 of cover
Keywords: Islam- Quran stories